Audit and feedback with or without training in-practice targeting antibiotic prescribing (TiPTAP): a study protocol of a cluster randomised trial in dental primary care - Goulao, Beatriz (Implement Sci, 2021)
BACKGROUND: Antimicrobial resistance is an increasingly serious threat to global public health and patient safety. Overuse of antibiotics has aggravated this issue. Around 7% of all antibiotics in Scotland are prescribed by dentists. Audit and feedback has been shown to decrease these prescriptions, but there is evidence that dentists still prescribe unnecessarily. Our aim is to compare the effectiveness of a theory-informed in-practice training session (TiPTAP) in addition to individualised audit and feedback, with audit and feedback alone for reducing antibiotic prescribing by NHS dentists working in NHS primary care dental practices. METHODS: We will conduct a 2-arm parallel cluster randomised trial: out of 228 practices, 114 will be randomised to the theory-informed in-practice training session targeting antibiotic prescribing and individualised audit and feedback; 114 practices will be randomised to audit and feedback alone. The theory-informed session will include (a) an introductory session including several behaviour change techniques; (b) problem solving discussion, setting and recording action plans; (c) practice-level prescribing feedback discussion. The primary outcome is the number of antibiotic items per 100 NHS treatment claims over a 1-year period post-randomisation for each dentist. Secondary outcomes are the number of amoxicillin 3 g and broad spectrum antibiotics prescribed per 100 NHS treatment claims over a 1-year period; amoxicillin 3 g and broad spectrum antibiotics defined daily doses of antibiotics per 100 claims. Process measures include fidelity, knowledge, and confidence. Primary and secondary outcomes will be obtained using routine data. DISCUSSION: This study provides the opportunity to robustly assess the effect of adding an in-practice training co-intervention to audit and feedback. Its behaviour change theory-informed content will allow replication of the different components and can inform future training interventions. TRIAL REGISTRATION: ISRCTN, ISRCTN12345678. Registered 18 June 2020.